2005
DOI: 10.1097/01.sap.0000139562.42726.dd
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Potential of Primed Periosteum Graft in the Rat Calvarial Model

Abstract: Repair of bone defects remains a major concern in plastic and maxillofacial surgery. Based on modern concepts of tissue engineering, periosteum has gained attention as a suitable osteogenic material. We tested the hypothesis that surgically released and immediately repositioned periosteum would exhibit high osteogenic capacity upon grafting in a rat calvarial defect. Seven days after periosteum was released from the tibia and immediately repositioned, the "primed periosteum graft" (PPG; n = 15) was placed into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 24 publications
4
31
0
2
Order By: Relevance
“…3,5,[77][78][79] Research has shown that net changes in periosteal strain during stance shift loading after surgery correlate to rapid de novo bone generation in critically sized defects. 13 Therefore, mechanical signaling at the tissue level may be responsible for the initiation of bone regeneration at the cellular level.…”
Section: Periosteum Tissue Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,[77][78][79] Research has shown that net changes in periosteal strain during stance shift loading after surgery correlate to rapid de novo bone generation in critically sized defects. 13 Therefore, mechanical signaling at the tissue level may be responsible for the initiation of bone regeneration at the cellular level.…”
Section: Periosteum Tissue Mechanicsmentioning
confidence: 99%
“…Although a number of studies have used native periosteum to heal critical size bone defects, 5,[77][78][79] alternatives are sought for the case when periosteum availability is limited. In many cases, native periosteum contains too few PDCs or has been damaged therefore limiting the tissue available for use.…”
Section: Bridging the Cell-tissue Level: Tissue Engineered Periosteummentioning
confidence: 99%
“…One study reported that bone formation was observed in the bone defect treated with periosteal cells from cultured medium within 35 days of grafting [3] . As in a previous study [12] , while new bone induced from the grafted tissue was detected in the bone defect, thisnew bone did not completely fill the defect by 35 days post grafting. The scaffold for osteoprogenitor cells serves to promote progenitor cell migration, proliferation and differentiation, as well as vascularization [3] is needed.…”
Section: Discussionmentioning
confidence: 48%
“…Geniş yüzeyli kemiklerin yüzeyinden vaskülarize periosteal flebin kaldırılması ile ototransplantasyon için gelişmiş iyileşme potansiyeline sahip, kullanışlı bir canlı yapı iskelesi elde edilebilir. 8 Kurashina ve ark., 19 27 Sonuç olarak; kemiğin kendi kendine iyileşme gösteremediği durumlarda iyileşmeyi sağlamak amacıyla çoğunlukla kemik greftleri olmak üzere çeşitli biyomateryaller kullanılmaktadır. Aynı şekilde osteojenik potansiyelinden dolayı peiosteum da greft materyali olarak tercih edilmektedir.…”
Section: 13unclassified